Creating universes with SAP BusinessObjects : create and maintain powerful SAP BusinessObjects Universes with the SAP Information Design Tool /: create and maintain powerful SAP BusinessObjects Universes with the SAP Information Design Tool. (2014) - Mahmoud, Taha M
No abstract available